Association of systemic inflammation with the serum apolipoprotein A-1 level: A cross-sectional pilot study - Tani, Shigemasa; Nagao, Ken; Hirayama, Atsushi (Journal of cardiology, 2016)
There is growing evidence to suggest that measurement of apolipoprotein A-1 (apoA-1), the main surface protein on high-density lipoprotein (HDL) particles, is superior to measurement of the serum HDL-cholesterol level as a predictor of the occurrence of coronary disease (CAD). We investigated the association of systemic inflammation as an initiator of CAD along with the serum apoA-1 level. This study was designed as a hospital-based cross-sectional study on 652 consecutive outpatients with at least one risk factor for CAD to investigate the relationships between the serum high-sensitivity C-reactive protein (hs-CRP) and the peripheral blood white blood cell (WBC) count and the serum apoA-1 level between April 2009 and October 2009. Multivariate analysis after adjustments for traditional coronary risk factors revealed reduced apoA-1 as an independent indicator of higher hs-CRP and WBC count, both in the overall subject population (β: −0.270 and −0.116, p<0.0001 and 0.003) and in a patient subset with serum low-density lipoprotein cholesterol <100mg/dL (β: −0.280 and −0.128, p<0.0001 and 0.045). However, in the patients who could be followed up 6 months later, the increase in the apoA-1 level was associated with a decrease in the hs-CRP level, but not with a decrease in the WBC count. Increased serum apoA-1 levels may be associated with decreased hs-CRP levels and decreased WBC counts as predictive inflammatory biomarkers of the onset of CAD. In particular, increase in the hs-CRP level and decrease in the apoA-1 level may be useful indices of the risk of CAD.